2013
DOI: 10.1099/jmm.0.060798-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, seasonality and severity of disease caused by pathogenic Escherichia coli in children with diarrhoea in Bolivia

Abstract: The prevalence of infection caused by different categories of diarrhoeagenic E. coli (DEC) strains, including enteroaggregative (EAEC), enteropathogenic (EPEC), enterotoxigenic (ETEC), enteroinvasive (EIEC) and enterohaemorrhagic (EHEC) E. coli, in children who suffered from diarrhoea (n53943) or did not have diarrhoea (n51026) were analysed in two areas in Bolivia over a period of 4 years. We also analysed the seasonality of DEC infections and severity of diarrhoea in children with DEC infection and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 50 publications
6
31
0
6
Order By: Relevance
“…This is consistent with the results of other studies [7,22]. It is worrying that ampicillin is still employed as one of the first line treatments in most low and middle-income countries [19,23].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results of other studies [7,22]. It is worrying that ampicillin is still employed as one of the first line treatments in most low and middle-income countries [19,23].…”
Section: Discussionsupporting
confidence: 92%
“…Bacterial count in river-water and -sediment varies with seasons being highest in summer [25,26]. Gonzales et al also reported seasonal variation in coliform bacteria displaying an increased prevalence during the rainy season [27]. The levels of indicator bacteria is a sign of level of contamination and thus of unhealthy water with high potential of health risk [28].…”
Section: Antibiotics Tested River-water N (%) River-sedimentn (%)mentioning
confidence: 99%
“…This is mainly due to a failure to isolate the causative agents in the laboratory or isolating one agent and leaving the other; both diagnostic factors affect the management and treatment of the disease. [32,36]. To effectively control diarrhoeal diseases in any community, an accurate understanding of the relative aetiologic agents and early detection of these agents using appropriate diagnostic tools is necessary.…”
Section: Introductionmentioning
confidence: 99%